Hemophilia in Indonesia: A Cost of Illness Analysis Using National Health Insurance Data (2022–2023) - Zahra, Adelia Pramesti; Permanasari, Vetty Yulianty; Nadjib, Mardiati; Nugraha, Erfan Chandra (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2026)
Hemophilia is one of the highest contributors to catastrophic costs in the National Health Insurance (NHI) program. This study aims to estimate the Cost of Illness (COI) of NHI participants with hemophilia from a payer and partial productivity loss perspective, using secondary data from BPJS Kesehatan to examine direct medical costs from the perspective of a third-party payer, and average hourly wages by province in Indonesia to assess patient productivity loss. The research method is a cross-sectional study using a quantitative design. The findings indicate that the average COI per participant was IDR 728,832,232. After applying sampling weights to estimate the national population, the total COI for hemophilia during 2022–2023 was IDR 3.02 trillion, with 99% attributable to direct medical costs. These findings indicate that although hemophilia affects a relatively small number of participants, it imposes a substantial financial burden on the NHI system. Significant differences in COI medians were observed across age, gender, length of stay, special drug usage, membership segmentation, ward class, hospital region, hospital type, treatment type, and severity. Hemophilia, as a high-cost, low-frequency condition, requires careful management to avoid further strain on NHI funding.